Intermediate Phenotype between ADULT Syndrome and EEC Syndrome Caused by R243Q Mutation in TP63 - Otsuki, Yuki (Plast Reconstr Surg Glob Open, 2016)
A patient who had ectrodactyly, dry skin, exfoliative dermatitis, and hypodontia with peg-shaped teeth, but not cleft lip and palate, is described. Ectrodactyly with a tooth anomaly is recognized in both acro-dermato-ungual-lacrimal-tooth (ADULT) syndrome and ectrodactyly-ectodermal dysplasia-cleft (EEC) syndrome. These 2 syndromes are caused by heterozygous mutations in the transcriptional factor gene p63. Mutation analysis of p63 gene showed a heterozygous mutation c.728G>A, p.Arg243Gln (previously referred to as R204Q) in the patient, but not in his parents. Therefore, this was a sporadic case of the p63 mutation–associated disorder. Although the mutation has been mostly reported in EEC syndrome patients, the present case did not have cleft lip and palate. Furthermore, the present case did not exhibit freckling or some of the other ectodermal dysplasia phenotypes typical of ADULT syndrome. The concept of ELA syndrome proposed by Prontera in 2011 resolves the problem confronted in diagnosing the present case. ELA syndrome is an acronym of EEC/limb–mammary syndrome/ADULT syndromes, and these 3 syndromes are united into a unique entity. This system can classify p63 mutation–associated disorders simply without interfering with treatment.